Phosphorus - A key element determining nitrous oxide emissions from boreal cultivated peat soil - Maljanen, Marja; Zheng, Yu; Pääkkönen, Minna; Voigt, Carolina; Louhisuo, Arja; Virkajärvi, Perttu (Soil biology & biochemistry, 2024)
Spatial variation in the emission rates of nitrous oxide (N2O) and methane (CH4) in soils can be significant due to the diverse biological, chemical, and physical conditions that influence the production and consumption of these gases. Drained organic soils are known to be hotspots for N2O emissions, and in wet conditions they can also emit CH4. We measured N2O and CH4 fluxes during the winter and growing season at 28 locations across a 7-ha area of drained organic agricultural soil in Eastern Finland. Our findings revealed expected high spatial and temporal variations in emission rates. The measured N2O emissions varied between −0.003 and 30.4 mg N2O m−2 h−1, averaging at 0.94 ± 3.00 mg N2O m−2 h−1 and CH4 emissions varied between −0.27 and 2.90 mg CH4 m−2 h−1, averaging at 0.10 ± 0.33 mg CH4 m−2 h−1. Phosphorus concentration was identified as a limiting factor and a critical determinant of spatial variations in N2O emissions, whereas CH4 emissions exhibited a decreasing trend with increasing sulphur and nitrate concentrations. Our study shows that N2O and CH4 fluxes are linked to other elemental cycles, making it critical to identify key nutrient-related processes that govern the spatial and temporal variability in emissions of these gases. [Display omitted] •High spatial variability of N2O and CH4 fluxes in cultivated boreal peat soils•Phosphorus rather than mineral nitrogen was a key predictor for N2O emissions•Substantial CH4 and N2O emissions can occur during the winter months•Soil nutrient status is critical to predict GHG emissions from cultivated peat soil